Does Audit Fee Moderate Influence of Audit Tenure and Auditor Switching to Acceptance of Going Concern Audit Opinion? - Handoko, Bambang Leo; Prasongko, Nathania Astria (International Journal of Psychosocial Rehabilitation, 2020)
In examining the financial statements the auditor must assess the ability of the company for the survival of its business. If it turns out there is potential for bankruptcy, the auditor will give a going concern audit opinion. The problem is that not all clients want to accept that opinion. Clients who do not want to receive, are disputed, sometimes choose to replace the auditor the following year. Our study tries to provide empirical evidence testing whether audit fees can moderate audit tenure and auditor switching to the going concern audit opinion. Our research is quantitative research, we use secondary data, namely companies going public in the manufacturing sector for the period of 2016 - 2018. Our data analysis method is path analysis. Our results state that audit tenure and auditor switching do not significantly influence the acceptance of going concern audit opinion. While the audit fee does not moderate the audit tenure but moderates the auditor switching of receiving going concern audit opinion